AB0474 A Prospective Evaluation of Endothelial Dysfunction in Systemic Lupus Erythematosus Patients without Previous Cardiovascular Events: Preliminary Results. (15th July 2016) - Taraborelli, M.; Sciatti, E.; Bonadei, I.; Terlizzi, V.; Fredi, M.; Zani, R.; Cancarini, G.; Tincani, A.; Franceschini, F.; Vizzardi, E.; Cavazzana, I.
Abstract : Background: Cardiovascular disease (CVD) due to premature atherosclerosis is a leading cause of morbidity and mortality in Systemic Lupus Erythematosus (SLE) patients. Early identification of patients with subclinical disease and tight control of cardiovascular risk factors are essential to reduce such complication [1, 2]. Objectives: To assess the prevalence of endothelial dysfunction (ED) by a non invasive procedure in SLE patients with early disease without history of CVD. Methods: SLE patients, according to 2012 Classification Criteria, with a disease duration less than 5 years, followed in the Rheumatology and Nephrology Unit of our Hospital were proposed to perform a cardiologic evaluation. Exclusion criteria were represented by: history of CVD, diabetes, chronic renal disease (creatinine clearance<60 ml/min), not controlled systemic arterial hypertension, current smoking or smoking in the last 3 years, hypercholesterolemia (total cholesterol>240 mg/dl), obesity (body mass index ≥30), statin or beta-blocker use. Each patient underwent a clinical and serological evaluation, a transthoracic doppler echocardiogram and an evaluation of endothelial function by endoPAT technique. Patients with ED, defined as reactive hyperemic index ≤2, were compared to those without ED by Fisher, T student or Mann-Whitney tests as appropriate. Results: We enrolled 17 SLE patients (100% female, 88% caucasian) with a median disease duration of 14 months (0–68), a mean age of 41 years (±16), and a mean age at diagnosis of 39 years (±17). Five patients (29%) had a systemic hypertension that was well controlled by treatment. No other cardiovascular risk factors were present. Disease characteristics and treatment are shown in Table I . Echocardiogram showed diastolic dysfunction in 3 patients. EndoPAT identified 7 patients (41%) with ED. We did not find any significant association between the presence of ED and demographic-clinical-serological characteristics of patients or treatments or echocardiografic findings. A tendency for an association with an history of renal disease was observed (57% versus 0%, p:0.058). Conclusions: A significant proportion of SLE patients showed signs of ED despite a recent disease and the absence of significant cardiovascular risk factors. References: Ramos-Casals M. The ill endothelium: how atherosclerosis begins in lupus. Rheumatology (Oxford) 2014; 53:583–5. Yildiz A, Soydinc S. Diastolic dysfunction and endothelial dysfunction in systemic lupus erythematosus. Rheumatol Int 2015;35:1281–2. Disclosure of Interest: None declared